قواعد تسوية منازعات الملكية الصناعية بواسطة التحكيم التجاري الدولي - الموسوي, علي فوزي (Journal of Legal Sciences, 2017)
it has emerged the role of commercial arbitration in disputes of industrial property in countries that have expanded the scope of industry property rights, Through the adopting material  rules in its domestic legislation , find their source in the established principles in international trade, and allow to settle all kinds of industrial property disputes , including the disputes relating to the validity of the patent or trademark by the International Commercial Arbitration.     The material  rules Concerned with the direct settlement of international trade disputes , But there are  material  rules specialized of settlement of industrial property disputes, including traditional material rule ( the international public policy) , and modern material rules such as freedom of the disposition of the rights rule , a financial nature  of the conflict rule and fair and equitable treatment to investors rule.